Pensiero tragico e pensiero ermeneutico - Ciancio, Claudio (Bollettino Filosofico, 2015)
Many philosophies take their origin from the state of uncertainty, contradiction, anguish of human condition. However in modern thought, apart from few cases (such as in Pascal), philosophies have been a strategy to avoid facing the tragic. In the nineteenth century and in the twentieth century there has been a revival of tragic thought. The present paper, however, focuses on an indirect dimension of the tragic, investing the condition of philosophical thought, namely the tension between objectifying thought and speculative thought, which today appears as the conflict between analytical and hermeneutical thinking, and is reflected within the hermeneutic thought. The full awareness of this contrast leads the speculative thought to take the form of paradox.